Polyarthritis following infusion of zoledronic acid: a case study - T. Campbell (Verduci Editore, 2023)
Objective: Osteoporosis is a skeletal disorder characterized by compromised bone strength which predisposes one to the development of fragility fractures. Bisphosphonates are the most commonly used medications for the treatment of osteoporosis. Zoledronic acid is a popular bisphosphonate due to its convenience and efficacy. The most common side effects of zoledronic acid include pyrexia, myalgia, arthralgia, headache, and flu-like symptoms. More severe side effects such as arthritis are rarely reported. The current case describes a patient with underlying osteoarthritis who experienced polyarthritis following an infusion with zoledronic acid. Case Presentation: A case of a 68-year-old female with osteoporosis on a background of osteoarthritis who experienced polyarthritis after receiving an intravenous zoledronate infusion is reported. Though this is a rare phenomenon, a review of the literature suggests that patients with pre-existing osteoarthritis may be more likely to develop arthritis after bisphosphonate exposure. Conclusions: The current case, therefore, highlights the importance of discussions with patients around additional side effects of zoledronic acid, especially in those with underlying degenerative arthritis.